Changes in number and weight of wheat and triticale grains to manipulation in source-sink relationship - Ballesteros Rodríguez, Elia; Martínez Rueda, Carlos Gustavo; Morales Rosales, E. J.; Estrada Campuzano, Gaspar; Gonzalez, Fernanda Gabriela (Hindawi, 2019)
The source-sink ratio experimental manipulation has helped to define whether a crop is limited by source or sink or co-limited by both. There is no evidence in triticale of source-sink manipulations effects on yield and yield components. Two experiments were accomplished during 2008 and 2009 growing seasons at the Universidad Autónoma del Estado de México, México, and one in 2010 at the National Institute of Agricultural Technology in Pergamino, Argentina. Two triticale cultivars (line 4 and 7) and one wheat cultivar (Tollocan) were used. Source-sink relations were modified at anthesis by thinning, degraining, shading, and total defoliation procedures. Changes in the source-sink relation affected yields in both species differentially. The changes in yield due to cultivars and treatments were explained mainly by the number of grains rather than by their individual grain weight. The number of grains was affected by all treatments in both species, while the individual grain weight was increased by thinning and degraining mainly in triticale. A greater number of fertile florets in triticale were associated with their higher rate of abortion compared to wheat. These results could help to better understand crop management and genetic improvement.